Comparison of Periodontal Status Between Male Exclusive Narghile Smokers and Male Exclusive Cigarette Smokers - Khemiss, Mehdi (Am J Mens Health, 2019)
Studies evaluating the effects of narghile use on the periodontium present conflicting conclusions. This study aimed to compare the periodontal status of exclusive narghile smokers (ENSs, n = 74) to that of exclusive cigarette smokers (ECSs, n = 74). Males aged 20–40 years were recruited to participate in this comparative study. Information concerning oral health habits (number of yearly visits to the dentist, daily toothbrushing frequency) and tobacco exposure were obtained. Clinical measurements were performed on all the existing teeth, except the third molars. The number of remaining teeth and decayed/missing/filled teeth (DMFT) were noted. The plaque levels were recorded using the plaque index of Löe and Silness. The gingival index modified by Löe was used to evaluate gingival inflammation. Teeth mobility was measured using bidigital mobility. The probing pocket depth was measured using a periodontal probe. Periodontal disease was defined as the presence of at least 10 sites with a probing depth ≥5 mm. Student’s t and chi-square tests were used to compare, respectively, the two groups’ quantitative and qualitative data. The two groups were matched for quantities of used tobacco, age, daily toothbrushing frequency, teeth mobility, number of remaining teeth, plaque index, and DMFT. Compared to the ECS group, the ENS group had a significantly lower number of yearly visits to the dentist (mean ± SD: 0.2 ± 0.5 vs. 0.1 ± 0.2), lower probing pocket depth (mean ± SD: 2.33 ± 0.63 vs. 2.02 ± 0.80 mm), and gingival index (median [interquartile]: 0.46 [0.10–0.89] vs. 0.00 [0.00–0.50]), and it included significantly lower percentages of smokers with periodontal disease (24.3% vs. 9.5%). In conclusion, chronic exclusive narghile smoking has fewer adverse effects on the periodontium than chronic exclusive cigarette smoking.